Catastrophic antiphospholipid syndrome. Pathogenesis issues - V. O. Bitsadze; D. K. Khizroeva; L. E. Idrisova; R. R. Abramyan; M. D. Andreeva; A. D. Makatsariya (Акушерство, гинекология и репродукция)
Сatastrophic antiphospholipid syndrome (CAPS) is an uncommon, often fatal, variant of the antiphospholipid syndrome that results in a widespread coagulopathy and high titres os antiphospholipid antibodies and affects predominantly small vessels supplying organs with the development of multiorgan failure. International approaches on terminology, risk factors, pathogenesis, criteria of diagnostics, clinical symptoms and management of patients with CAPS are reviewed. Own clinical experience of management 17 patients with CAPS development also presented. CAPS is life-threatening condition but optimal treatment for CAPS is not developed yet. CAPS presents a multidisciplinary problem.